Visually Challenged International League Participations In World Championship 1990 – 2018 - Ibrahim, Huda; Nazar, Raheeq (Journal of Physical Education, 2018)
Visually Challenged International League Participations In World Championship 1990 – 2018The study aimed at identifying the participation of the international league for the visually challenged in World championships. In addition to that the researcher aimed at identifying the history of Iraqi Paralympic committee. The problem of the research lies in the lack of historical studies about visually challenged athletes. The researcher used the descriptive method. The results showed a great legacy of medals in athletics for visually challenged athletes. The researcher came up with the conclusions and recommendations. The research problem focused on asking the following question : What are the problem of the Iraqi national team for people with visual disabilities in world championships ? and what are the problems and difficulties that have been addressed to the players during the training and the competition? The aim of the research was to identify the emergence of the Iraqi Paralympic committee and to identify the results of the world championships of visually impaired people and after the historical narrative of the researcher concluded that research in the field of sports has moved away from the historical studies that resulted in fewer historical sources. She recommended concentrating on historical studies and providing efficient training means as well as developing a comprehensive diet plan for each player.